Fungsi Website Dalam Pelayanan Publik (Studi Efektivitas Website Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Malang) - Agung Surya Pratama (Jurnal Administrasi Publik, 2013)
Abstract: Websites functions in public services (A study of the effectiveness of the website at the Department of Population and Civil Records, Malang Regency). This research was undertaken because of the importance of the need for technology and information in services. Websites are one form where services utilize technology, information and communication, for the purpose of providing information and as a tool for communicating effectively. The Department of Population and Civil Records, is one instance of the government utilizing websites as a tool for delivering information and communicating with the community. This research is descriptive and qualitative. The problems are (1) The function of the website at the Department of Population and Civil Records, Malang Regency (2) The effectiveness of the website at the Department of Population and Civil Records (3) The factors that limit the implementation of the website’s functions. The outcome from this research is that the function of this website is for communication and information. However there are several factors that cause obstacles in the performance of the website’s functions. Keywords: website, public service   Abstrak : Fungsi Website Dalam Pelayanan Publik (Studi Efektivitas Website Pada Dinas Kependudukan dan Catatan Sipil Kabupaten Malang). Penelitian ini dilakukan karena pentingnya kebutuhan teknologi dan informasi dalam pelayanan. Pelayanan menggunakan teknologi informasi dan komuikasi salah satu bentuknya adalah website, hal ini berguna dalam pemberian informasi dan sarana komunikasi secara efektif. Dinas Kependudukan dan Catatan Sipil merupakan instansi pemerintahan yang memanfaatkan website sebagai sarana penyampaian informasi dan komunikasi dengan masyarakat Penelitian ini bersifat deskriptif dengan pendekatan kualitatif. Fokus permasalahannya adalah (1) Fungsi website pada Dinas Kependudukan dan Catatan Sipil Kabupaten Malang (2) Efektivitas Fungsi website pada Dinas Kependudukan dan Catatan Sipil Kabupaten Malang (3) Faktor kendala dalam pelaksanaan fungsi website. Hasil dari penelitian ini adalah fungsi website yang terjadi ada Dinas Kependudukan dan Catatan Sipil Kabupaten Malang adalah dalam komunikasi dan informasi. Namun ada beberapa faktor penghambat dalam pelaksanaan fungsi website.   Kata kunci: website, pelayanan publik